2012
DOI: 10.1016/j.sleep.2011.06.020
|View full text |Cite
|
Sign up to set email alerts
|

TCRA, P2RY11, and CPT1B/CHKB associations in Chinese narcolepsy

Abstract: Objectives Polymorphisms in the TCRA and P2RY11, two immune related genes, are associated with narcolepsy in Caucasians and Asians. In contrast, CPT1B/CHKB polymorphisms have only been shown to be associated with narcolepsy in Japanese, with replication in a small group of Koreans. Our aim was to study whether these polymorphisms are associated with narcolepsy and its clinical characteristics in Chinese patients with narcolepsy. Methods We collected clinical data on 510 Chinese patients presenting with narco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 27 publications
4
31
0
Order By: Relevance
“…Genetic associations [10], [11], [12], [13], [14], [15], [16], presence of anti-tribbles 2 antibodies [17], [18], [19] and other recent observations [20], [21] suggest that autoimmune mechanisms are involved in the etiopathogenesis of narcolepsy [22], [23], [24]. Seasonality of onset [25] and reports of an association to preceding streptococcal infections [26], [27] have suggested a link with upper respiratory tract infections.…”
Section: Introductionmentioning
confidence: 93%
“…Genetic associations [10], [11], [12], [13], [14], [15], [16], presence of anti-tribbles 2 antibodies [17], [18], [19] and other recent observations [20], [21] suggest that autoimmune mechanisms are involved in the etiopathogenesis of narcolepsy [22], [23], [24]. Seasonality of onset [25] and reports of an association to preceding streptococcal infections [26], [27] have suggested a link with upper respiratory tract infections.…”
Section: Introductionmentioning
confidence: 93%
“…These researchers suggested that variations in the CPT1B/CHKB susceptibility genes are thought to play a role in sleep regulation and were a common genetic susceptibility factor to narcolepsy in the East Asian population. However, this finding was not replicated in Chinese narcolepsy samples (Han et al, 2012), indicating that the association of SNP harboring between CPT1B and CHKB with narcolepsy susceptibility is still speculative. They also reported that rs5770917 has strong linkage disequilibrium with rs5770911, rs2269381, rs2269382 SNPs according to the HapMap data for individuals of Japanese ancestry (Miyagawa et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…However, the susceptibility found in the Japanese and Korean samples was not replicated in Chinese narcolepsy samples (Han et al, 2012). A protein encoded by the CPT1B gene is the rate-controlling enzyme of the longchain fatty acid (-oxidation pathway in muscle mitochondria (McGarry and Brown, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…TCR alpha and beta loci are strongly associated with narcolepsy [9, 11, 67, 75]. Furthermore, variants in Cathepsin H ( CTSH ), an enzyme that process peptides for presentation by HLA on dendritic cells, and TNFSF4 a molecule regulating immune cell fate, are associated with narcolepsy [9].…”
Section: Genetic Variants At the Hla Region Predispose To Narcolepsymentioning
confidence: 99%
“…Furthermore, variants in Cathepsin H ( CTSH ), an enzyme that process peptides for presentation by HLA on dendritic cells, and TNFSF4 a molecule regulating immune cell fate, are associated with narcolepsy [9]. Finally, variants located within the interferon receptor region ( IL10RB-IFNAR1 ), the purinergic receptor ( P2RY11 ), the ZNF365 transcription factor as well as chemokine receptor CCR1-CCR3 regions are associated with narcolepsy [9, 75, 76]. As all these genetic loci have been associated with immune function or other autoimmune disorders, pathway analysis clearly demonstrate narcolepsy is likely autoimmune.…”
Section: Genetic Variants At the Hla Region Predispose To Narcolepsymentioning
confidence: 99%